Sunan Ampel dan Nilai Etis Islam Nusantara: dari Tantra-Bhairawa kepada Praktik Keagamaan Nir-Kekerasan - Mukaffa, Zumrotul (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This article focuses its discussion on the order of ethical values behind the success of Sunan Ampel, one of the Nine Saints (Walisongo), to co-modify the Pancamakara ritual that involves the Tantra-Bhairawa sect during the era of Majapahit Kingdom. The Pancamakara has been also called as Pancamakara Puja, Cakra Puja, Mo-Limo or Panca Ma, which stand on five basic elements, namely mamsa, matsya, madya, maithuna, and mudra. The study finds that Sunan Ampel had successfully created the concept of Pancamakara and its sustainability as exchange values with Islam with no intention to totally deconstruct its utility values. The value order consists of certainty to always emphasize islamization and to bridge Islam and local religious rituals in order to achieve peaceful and non-violent religious practices. The value order is transformed into existing pattern of culture. Consequently, the implementation pattern of Pancamakara as religious ritual had still been preserved but its substance was entirely deconstructed. Through his magical touch, Sunan Ampel had preserved Pancamakara that had no longer based on the five basic elements called Mo-Limo. Instead, the doctrine commands people to avoid the five basic elements and it now becomes Moh-Limo (unwilling to commit five immoral acts).